The Role of the Family in Preventing Relapse in Mentally Ill Patients - Septirina, Septirina; Reni, Reni; Assidiq, Assidiq (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
Mental disorders are manifestations of behavioral deviations due to emotional distortion, resulting in abnormal behavior. This occurs because of the decline in all mental functions. Curative efforts in the form of collaboration with other health teams to provide treatment and rehabilitative efforts can help patients in their daily activities, so that they can return to normal life. Interventions for families are intended to strengthen the family system, prevent or inhibit relapse, and maintain clients in the community. This research method uses a descriptive case study design that aims to create systematic descriptions, images, paintings where data collection uses interviews, observations, documentation and demonstrations. The results of this study indicate that by providing information to families about the disease, suggesting effective coping mechanisms and psychoeducation programs, it can reduce the tendency of clients to relapse and reduce the influence of this disease on other families.